Reimagining social medicine from the south - Neely, Abigail H. 1979- (Duke University Press, 2021)
In Reimagining Social Medicine from the South, Abigail H. Neely explores social medicine's possibilities and limitations at one of its most important origin sites: the Pholela Community Health Centre (PCHC) in South Africa. The PCHC's focus on medical and social factors of health yielded remarkable success. And yet South Africa's systemic racial inequality hindered health center work, and witchcraft illnesses challenged a program rooted in the sciences. To understand Pholela's successes and failures, Neely interrogates the "social" in social medicine. She makes clear that the social sciences the PCHC used failed to account for the roles that Pholela's residents and their environment played in the development and success of its program. At the same time, the PCHC's reliance on biomedicine prevented it from recognizing the impact on health of witchcraft illnesses and the social relationships from which they emerged. By rewriting the story of social medicine from Pholela, Neely challenges global health practitioners to recognize the multiple worlds and actors that shape health and healing in Africa and beyond